Speakezio Application as an Alternative and Augmentative Communication Media for Cerebral Palsy Students - Eliyas, Andri; Susetyo, Budi; Nursaniah, Sofi Septiani Julaeha (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
The obstacle experienced by most children with cerebral palsy is limited communication skills. This is due to disorders of the speech organs or limitations in receptive and expressive language abilities experienced by children with cerebral palsy. So, when communicating, you need alternative augmentative media or communication systems (AAC) that can help you communicate. This research aims to develop the Speakezio application as AAC media. The method used is the RD (Research and Development) research method with a qualitative approach. This research involves one subject (single subject) which is used as a model in developing applications. This research obtained results in the form of the Speakezio application which was developed based on the results of assessments on target subjects and trials of the application as a media for the AAC system. The trial results show that this application can improve children's receptive and expressive language skills. Apart from that, this application can help communication between children and parents so that parents can more easily understand the messages conveyed by children.